The degree of kindergarten teachers' employment of artistic activities in raising awareness of the spread of the new Corona virus (Covid-19) from the teachers and headmasters point.(a field study in Tartous city) - سليمان, هلا (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The research aims to know the degree to which kindergarten teachers employ artistic activities in raising awareness of the spread of the new Corona virus (Covid-19)from the teachers and headmasters point, The research aims to know the differences between the teachers in using art activities according to the variables:, (functional title ,years of experience, educational qualification ,school type) And to achieve the goal of the research, the descriptive method was used, and the sample included (104) teachers and (38) headmasters in kindergarten Tartous ,for the academic year 2021/2022. A questionnaire has applied which measures the degree of female teachers' employment of artistic activities in raising awareness of corona virus, and it included (32) phrases. And it reached several results, the most important of which are: The degree of kindergarten teachers' employment of artistic activities in raising awareness of the spread of Corona virus (Covid-19) from their point of view is a high degree. . The degree of kindergarten teachers’ employment of artistic activities in raising awareness of the spread of Corona virus (Covid-19) from the headmasters point , it ranged between high to medium degree. Lack of the difference in the degree to which kindergarten teachers employ the artistic activities in raising awareness of the spread of the new Corona virus (Covid19) according to the job title variable and the variable of experience years. . Having a difference in the degree to which kindergarten teachers employ the artistic activities in raising awareness of the spread of Corona virus (Covid19). according to the private kindergartens. . Having a difference in the degree to which kindergarten teachers employ the artistic activities in raising awareness of the spread of corona virus(Covid19) depending on the educational qualification variable, for the benefit of university degree holders.